1986
DOI: 10.1103/physreva.33.319
|View full text |Cite
|
Sign up to set email alerts
|

Photoemission from the3dand3psubshells of Kr

Abstract: Partial photoionization cross sections and angular-distribution asymmetry parameters were determined for Kr 3d photoemission using photon energies of 100 to 280 eV (to 800 eV for the asymmetry parameter). For the 3p subshell, the branching ratio relative to the 3d cross section and the asymmetry parameter were measured using energies of 280 to 800 eV. These results show good agreement with Hartree-Fock-theory predictions at all photon energies. The summed intensity of 4p~np satellites relative to the 3d main l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
46
2

Year Published

1986
1986
2007
2007

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 65 publications
(55 citation statements)
references
References 27 publications
7
46
2
Order By: Relevance
“…Electron angular anisotropy parameter p for the N2 Is photoline from threshold to hv= 450 eV. Measurements by Kempgens [14] and Lindle [15] did not take non-dipolar effects into account and deviate from our measurements.…”
Section: Resultscontrasting
confidence: 62%
“…Electron angular anisotropy parameter p for the N2 Is photoline from threshold to hv= 450 eV. Measurements by Kempgens [14] and Lindle [15] did not take non-dipolar effects into account and deviate from our measurements.…”
Section: Resultscontrasting
confidence: 62%
“…3,6,7,29 The term ''shakeup'' is used here in a limited sense to refer only to correlation peaks that exhibit a particular photon energy dependence in their cross sections as discussed by Becker and Shirley. 3 Several experimental and theoretical studies on atomic systems [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] have indicated that the phenomenological classification of correlation states into intrinsic and dynamic correlations is very useful in understanding the complexity of electron-electron interactions. Recent studies on molecular systems [23][24][25][26][27][28] have also shown that the Becker-Shirley classification is feasible.…”
Section: Introductionmentioning
confidence: 99%
“…In such recapture processes small exchange energies should be favored by the system, leading to the population of the singly ionized 4p 4 nl states with the highest n-the states which are just below the double ionization thresholds ͑Table II, the 4p 4 energies for clusters have been obtained by subtracting the shifts observed in Ref. 30,31 Quantitatively it all means that, whatever pathway leads to the population of the higher n final states, resonant excitation or recapture, its probability is similar across the threshold and is low in comparison with the case of n =5,6. In analogy to Kr atoms, 6 singly ionized 4p 4 nl states with n Ͼ 11 in clusters would be so close to each other that they could merge in a spectral pattern resembling a single or double broad peak which gradually transforms into the PCI-influenced Auger peaks when the photon energy exceeds the threshold.…”
Section: Photoelectron Recapturementioning
confidence: 99%